A Tomato Lycopene Complex Protects the Kidney From Cisplatin-Induced Injury via Affecting Oxidative Stress as Well as Bax, Bcl-2, and HSPs Expression - Dogukan, Ayhan; Tuzcu, Mehmet; Agca, Can Ali; Gencoglu, Hasan; Şahin, Nurhan; Onderci, Muhittin; Şahin, Kazım (Routledge Journals, Taylor & Francis Ltd, 2011)
Cisplatin-induced nephrotoxicity is related to an increase in oxidative stress in the kidney. Lycopene, a carotenoid found in tomatoes, is a potent dietary antioxidant. In the present study, we investigated the effect of the tomato lycopene complex against cisplatin-induced lipid peroxidation and nephrotoxicity in rats. Male Wistar rats (n = 28, 8 wk old, between 200-215 g) were divided into 4 groups: (a) control, (b) tomato lycopene complex (6 mg/kg, daily; consisting of 6% lycopene, 1.5% tocopherols, 1% phytoene and phytofluene, and 0.2% -carotene), (c) cisplatin (7 mg/kg i.p., single dose), and (d) cisplatin + tomato lycopene complex. Cisplatin administration increased serum urea-N (171 vs. 37 mg/dl) and creatinine (1.80 vs. 0.42 mg/dl) and decreased body weight in comparison with the control rats (P 0.001). Serum creatinine and urea-N levels were lower in rats treated with tomato lycopene complex + cisplatin compared with rats treated with cisplatin alone (P 0.001). The renal tissue from the cisplatin-treated rats had greater malondialdehyde (MDA; 172 vs. 93 nmol/g) and 8-isoprostane levels (1810 vs. 610 pg/g) than that from the control rats (P 0.001). Tomato lycopene complex prevented the rise of MDA and 8-isoprostane (P 0.001). No measurable lycopene could be detected in the serum of the control and cisplatin-treated rats, whereas lycopene was observed in the serum of rats supplemented with tomato lycopene complex. Renal Bax protein expression was significantly higher in the cisplatin-treated rats than in the control rats, and tomato lycopene complex treatment significantly reduced Bax expression (P 0.001). The expression of Bcl-2 was higher in tomato lycopene complex/cisplatin-treated rats than in the cisplatin-injected rats (P 0.05). The expression of renal HSP60 and HSP70 was significantly lower in tomato lycopene complex + cisplatin-treated rats than in rats treated with cisplatin alone (P 0.001). These results suggest that tomato lycopene complex has protective effects against cisplatin-induced nephrotoxicity and lipid peroxidation in rats.
Keywords: Acute-Renal-Failure; Induced Nephrotoxicity; Lipid-Peroxidation; in-Vivo; Powder Supplementation; Prostate-Cancer; Ascorbic-Acid; Rat-Kidney; Cell-Death; Heat-Shock